Performance Assessment of Bondoyudo Watershed Management - Hery Budi Sulaksono; Gusfan Halik; Retno Utami Agung Wiyono (U Karst, 2021)
Continues decrease of vegetation will result in a high erosion and sedimentation rate in the Bondoyudo watershed. This will result in reduced water retention capacity and accelerate land degradation. This study aims to monitor and evaluate the performance conditions of the Bondoyudo watershed according to the assessment parameters of the weighting criteria, which include land criteria, water management criteria, socio-economic criteria, water construction investment criteria, and space utilization criteria. Information about the upper part, middle part, and lower part of Bondoyudo River is collected from primary data, secondary data, and analysis results. The score of the watershed evaluation's carrying capacity is obtained from the results of the analysis from each weighting and scoring value of each criterion and sub-criteria. Watershed performance classifications are obtained by adding up the scores of each criterion. The watershed classification's total score is 103.25, which is classified as a medium recovery level category. It necessary to manage and restore the carrying capacity of the Bondoyudo watershed in supporting the development of water resources so that there is no decline in the performance of the Bondoyudowathersed. Recommended activity plans are water resources conservation, and utilization integrated control and involving stakeholders in watershed management